Moisture Use Efficiency of- Wheat as Influenced by Seeding Rate and Row Spacing Under Limited Moisture Condition - Srivastava, V.C.; Sidique, M. (Journal of Soil and Water Conservation, 2022)
Rainfall, because of its erratic distribution, is more of a curse than a boon in the plateau regions of Bihar. We can not make the monsoon behave or co-operate the way we desire, but we can learn to live with them. It involves the needed adjustments in management practices of most adopted crops and their varieties. Since rainfall during the period October to March is low and exceedingly variable, the availabe soil moisture depends primarily on the moisture accumulated in the soil during preceeding rainy season and rain fed crop aenerally its grows orttogeny on decreasing soil moisture status. The advent of high yielding short duration varieties of wheat has necessiated the possibility and feasibility upgrading and updating crop production in this region by suitable varieties for their ability to economic yield under limited moisture coadition, Plant population in a unit area is intimately connected with the competition for the use of soil moisture, plant nutrients and solar energy.